LEXICAL AND NUMERICAL EXPRESSIONS OF THE NUMBER GROUP OF THE SOGDIAN LANGUAGE - Исхаков М. М.; Ғойибов Б. С. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the significance of numbers, lexical, and numerical expressions for the historical process based on Sogdian sources. The authors accompany each number with a graphical representation of the numbers in Sogdian texts. Based on the representation of numbers in the texts, they were analyzed by counting, ordering, and categorizing them. The scientific nature of the study was further enhanced by an analysis of the pronunciation of numbers found in Sogdian documents in Old Persian, Avestan and Iranian. The introductory section of the article reflects the relevance of the problem, while the main part analyzes numbers from 1 to 1000 based on existing sources. The conclusion presents aspects related to the disappearance of the Sogdian language, but the persistence of these numbers in modern dictionaries.